2007
DOI: 10.1002/mpr.208
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the World Health Organization Adult ADHD Self‐Report Scale (ASRS) Screener in a representative sample of health plan members

Abstract: The validity of the six-question World Health Organization Adult ADHD Self-Report Scale (ASRS) Screener was assessed in a sample of subscribers to a large health plan in the US. A convenience subsample of 668 subscribers was administered the ASRS Screener twice to assess test-retest reliability and then a third time in conjunction with a clinical interviewer for DSM-IV adult ADHD. The data were weighted to adjust for discrepancies between the sample and the population on socio-demographics and past medical cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
608
6
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 636 publications
(659 citation statements)
references
References 31 publications
23
608
6
10
Order By: Relevance
“…To capture the level of ADHDlike behavior, we calculate the average score of the ASRS-6 screener. The Cronbach's a for the ASRS-6 scale amounts to 0.58, which is relatively low but still close to the lower bound of reported alphas for the ASRS screener questions in Kessler et al (2007).…”
Section: Independent Variablesupporting
confidence: 63%
See 1 more Smart Citation
“…To capture the level of ADHDlike behavior, we calculate the average score of the ASRS-6 screener. The Cronbach's a for the ASRS-6 scale amounts to 0.58, which is relatively low but still close to the lower bound of reported alphas for the ASRS screener questions in Kessler et al (2007).…”
Section: Independent Variablesupporting
confidence: 63%
“…The ASRS-6 is a short form of the 18-item patient-reported ASRSv1.1 questionnaire, assessing the frequency of all 18 DSM-IV symptoms of ADHD. The ASRS-v1.1 scale has been proven effective in screening for adult ADHD (Kessler et al 2005(Kessler et al , 2007Matza et al 2011). …”
Section: Independent Variablementioning
confidence: 99%
“…Parental ADHD was assessed using the ADHD Self-Report Scale. 24,25 Parents provided consent and children assent.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in adults with ADHD find lifetime rates of alcohol use disorders (AUD) ranging between 21.0% and 53.0% (4,5), whereas previous studies found the prevalence of high risk of ADHD to be ranging between 21.0% and 23.1%, according to screening test (6)(7)(8). In an international multi-center study using the Adult ADHD Self-Report Scale (ASRS) (9,10), adult ADHD prevalence was found to be lower among treatmentseeking patients with AUD than among patients with drug use disorder (11). Nevertheless, a history of ADHD in childhood increases the risk of developing AUD by a factor of 1.74 (12), 1.35 (13), or 1.51 (14).…”
Section: Introductionmentioning
confidence: 99%